Structural insight into protein–protein interactions between intestinal microbiome and host. (June 2022) - Post, Sarah E.; Brito, Ilana L.
Abstract: Protein–protein interactions between the microbiome and host organism play an important role in shaping host health. These host-modulating proteins have therapeutic potential in treating microbiome-linked disorders such as inflammatory bowel disease and obesity. Structural analysis of interacting proteins provides highly mechanistic insight into the domains driving these interactions and the resulting influence on host cell processes. Here, we briefly review recent publication of microbiome protein structures involved in host binding interactions, the effects of these interactions on host physiology, and the need for further study to increase the ability to detect proteins with therapeutic potential. Highlights: Structural analysis of proteins from probiotic and commensal bacteria reveals host-binding functions. Proteins from these beneficial microbes modulate host physiology independently of the whole bacterium, indicating therapeutic potential. Further structures of microbiome proteins will improve identification of host-interacting functions in large datasets.